1983
DOI: 10.7164/antibiotics.36.1439
|View full text |Cite
|
Sign up to set email alerts
|

New fluorinated erythromycins obtained by mutasynthesis.

Abstract: Following the previously described semisynthetic preparation of new aglycones (8S)-8fluoroerythronolide A (I), (8S)-8-fluoroerythronolide B (II) and the monoglycoside 3-0mycarosyl-(8S)-8-fluoroerythronolide B (III), their conversion into new fluoroerythromycins was attempted by mutational biosynthesis. The strain Streptomyces erythraeus ATCC 31772, a mutant blocked in the biosynthesis of erythromycin, was employed in the present investigation. Four new antibiotics, (8S)-8-fluoroerythromycin A (IV), (8S)-8-fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Although few publications have reported the antibacterial activity of flurithromycin, it appears to be very similar to erythromycin in vitro (41); activity against staphylococci, streptococci, H. influenzae, and B. catarrhalis was approximately the same as that of erythromycin (37,61,76). One study reported some improvement in activity against anaerobic bacteria (37).…”
mentioning
confidence: 99%
“…Although few publications have reported the antibacterial activity of flurithromycin, it appears to be very similar to erythromycin in vitro (41); activity against staphylococci, streptococci, H. influenzae, and B. catarrhalis was approximately the same as that of erythromycin (37,61,76). One study reported some improvement in activity against anaerobic bacteria (37).…”
mentioning
confidence: 99%
“…Since its introduction in 1952 (25). A-62671 is the major metabolite of clarithromycin in humans, and dirithromycin is a prodrug of erythromycylamine.…”
mentioning
confidence: 99%
“…In one study, semi-synthetic erythromycin aglycones were fed to a Saccharopolyspora erythraea (Streptomyces erythraeus) strain blocked in erythromycin production, leading to the production of 8-fluoroerythromycins (Toscano et al 1983). These novel analogues possessed comparable antibiotic activity to the parent compounds, but higher levels were present in the serum and tissue (Benoni et al 1988).…”
Section: Precursor-directed Biosynthesis and Mutasynthesismentioning
confidence: 99%